Determination of plasma fibrinogen in pregnant women during labor and postpartum - Quesada V., Norberto (1971)
We have determined the value of plasma fibrinogen in 200 women, grouped into eight sections of 25 each. The results obtained in normal nonpregnant women, pregnant women in the first, second and third trimester, during labor and in the first, second and third day postpartum compared. Statistically significant increase was observed when fibrinogen values ​​of normal non-pregnant women with the values ​​of pregnant women in the second and third quarter, labor and on the first day postpartum compared.